To Whom Should I Send it? Sender Perspective on Incentivized Word of Mouth - Tercia, Christiana Yosevina; Teicher, Thorsten (Universitas Prasetiya Mulya, 2020)
This paper examines how consumers’ WOM-related activity can be steered by marketing measures. By conducting an experimental study using mobile coupons as a novel tool of word of mouth, we specifically investigate how monetary incentives foster senders’ decision in targeting particular receivers. Our results show that senders tend to share incentivized WOM with receivers deemed to be close to them when the amount of the incentive is unequal between sender and receiver, and information on the incentive is revealed to both sides. The different amount of incentive for senders and their receivers also leads senders to target receivers who are deal prone.